Prodromus of a fern flora for Bolivia. XXXVIII. Tectariaceae - Kessler, Michael; Smith, Alan R. (Phytotaxa, 2018)
We provide a synopsis to the family Tectariaceae in Bolivia, including 17 species in four genera. The main genus, Tectaria, has 12 species. Despite being one of the most common and conspicuous fern genera in humid lowland forests, it remains challenging, and further study will likely result in taxonomic changes for Bolivia.